Kathryn A. Woolard, «Singular and Plural. Ideologies of Linguistic Authority in 21st Century Catalonia», Oxford / Nova York, Oxford University Press, 2016, 365 pp. - Nicolás, Miquel (Caplletra. Revista Internacional de Filologia, 2017)
Ressenya sobre el llibre de Kathryn A. Woolard, Singular and Plural. Ideologies of Linguistic Authority in 21st Century Catalonia, Oxford / Nova York, Oxford University Press, 2016, 365 pp., ISBN: 978-0190258627.